Entre a teoria e a prática na formação inicial de professores: contribuições do programa residência pedagógica - Silva, Joselma (2020)
The initial teacher training process is considered a challenging task as it seeks to articulate theory and practice and prepare undergraduate students to the educational reality, since, throughout the teaching career, the reconstruction of new thoughts and new perspectives is required. Based on this assumption, this research starts from the following question: How initial training can be contemplated, in teaching programs, in order to guarantee to the students training closer to the teaching profession, with a view to the active exercise between theory and practice, and to strengthen the relation between the University and the primary school? Faced with such problems, this research had as objective to analyze the descriptive reports of the activities carried out by students of the Pedagogy degree course, who were part of the Pedagogical Residency Program, in order to understand which actions impacted or contributed to the initial teacher training process. The research presented a qualitative approach based on a documentary research carried out in a public school in the municipality of Lavras. Therefore, the object of study consisted of monthly reports produced by eight students of the Pedagogy course at the Federal University of Lavras, scholarship holders of the Pedagogical Residency Program, in the period from 2018 to 2020. And to solidify this study, a theoretical basis is sought in the proposals of André et al. (2016), Garcia (2009), Gatti (2013, 2016, 2019), Nóvoa (1992, 2007, 2009, 2017), Pimenta (2012), Tardif (2000, 2002, 2009) and Zeichner (1993, 2010), who discuss about teacher training process, among others. The study reflected on the pedagogical actions experienced and their repercussions for the initial teacher training by the activities reports analysis developed during the Pedagogical Residency Program (PRP). The actions were identified from three formative dimensions: “observation”, “intervention” and “action reflection”, which were interconnected, as they aim at professional development within the school context. The research results allowed us to think about some issues, such as strengthening of the relation between the University and the school, promoting dialogues and approximations; the articulation between theory and professional teaching practice; the wide, concrete and active experience, based on the school context experiences, which favored critical reflection on the teaching challenges, as well as their contributions to education.